Penegakan Hukum Terhadap Kejahatan Penyebaran Konten Porno Balas Dendam (Revenge Porn) - Salmon, Harly Clifford Jonas (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
The dissemination of pornography is regulated by the pornography law, and the offense of decency is regulated in the Criminal Code. Articles 281, 282, 283, 532, and 533 of the Criminal Code prohibit pornography and pornographic acts and provide punishment. The Law Number 19 of 2016 specifically regulates decency in the electronic field, amending the Law Number 11 of 2008 concerning Electronic Information and Transactions. Komnas Perempuan reported an increase in gender-based violence on the internet, specifically revenge porn, with cases increasing from 126 in 2019 to 510 in 2020. Law enforcement efforts against perpetrators of revenge pornographic content on social media include preventive and repressive measures.